Estudio de la influencia de la ESPAM MFL y su impacto socioeconómico en el sector comercial en la Ciudad de Calceta. - Alcívar Falcones, Jéssica Alejandra (2015)
In order to determine the influence of the Agricultural Polytechnic School of Manabí Manuel Félix López and its socio-economic impact in the commercial sector of Calceta during the period of 2012-2014; the study started with the identification of the established businesses in the jurisdiction of the Department of valuation and land registry of the Municipal Government of Bolivar, until 2015 there are 267 businesses registered in the database; a sample of 58 owners answered a questionnaire to measure the socio-economic impact; obtaining 34 businesses that were created before or since the establishment of the university and 24 businesses during the study period; 18 merchants have academic preparation of third and fourth degree that supports administrative and financial business decisions, in counterpart 40 owners have basic knowledge, however only 10 came frequently to the trainings provided by the university; with respect to the capital only 10 dealers are in recovery period and 48 already increased by using strategies to meet the needs of students who have settled in Calceta, for the 58 owners generated opportunities for entrepreneurship and employment sources; by influence of the university also generated profits during 2012 and 2013 were 4.000-5.000 dollars but increased to 5.000-6.000 dollars in 2014, providing economic stability to the owners of the businesses that make up the commercial sector of Calceta.